2021
DOI: 10.3390/ijms222413543
|View full text |Cite
|
Sign up to set email alerts
|

Infection by High-Risk Human Papillomaviruses, Epithelial-to-Mesenchymal Transition and Squamous Pre-Malignant or Malignant Lesions of the Uterine Cervix: A Series of Chained Events?

Abstract: Wound healing requires static epithelial cells to gradually assume a mobile phenotype through a multi-step process termed epithelial-to-mesenchymal transition (EMT). Although it is inherently transient and reversible, EMT perdures and is abnormally activated when the epithelium is chronically exposed to pathogens: this event deeply alters the tissue and eventually contributes to the development of diseases. Among the many of them is uterine cervical squamous cell carcinoma (SCC), the most frequent malignancy o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 273 publications
(483 reference statements)
0
26
0
Order By: Relevance
“…Cancer-associated EMT is a multistep process, which begins with the loss of apicobasal polarity in epithelial cells, followed by the loss of adherens and tight junctions, epithelial markers, and cell adhesion. During the final stages of EMT, cells acquire a spindle cell morphology and express mesenchymal markers ( 14 19 ). Cells in intermediate stages of EMT may express both epithelial E-cadherin and mesenchymal vimentin markers and thus present a hybrid phenotype; this is a critical factor contributing to the invasiveness of cancer cells ( 14 19 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cancer-associated EMT is a multistep process, which begins with the loss of apicobasal polarity in epithelial cells, followed by the loss of adherens and tight junctions, epithelial markers, and cell adhesion. During the final stages of EMT, cells acquire a spindle cell morphology and express mesenchymal markers ( 14 19 ). Cells in intermediate stages of EMT may express both epithelial E-cadherin and mesenchymal vimentin markers and thus present a hybrid phenotype; this is a critical factor contributing to the invasiveness of cancer cells ( 14 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…During the final stages of EMT, cells acquire a spindle cell morphology and express mesenchymal markers ( 14 19 ). Cells in intermediate stages of EMT may express both epithelial E-cadherin and mesenchymal vimentin markers and thus present a hybrid phenotype; this is a critical factor contributing to the invasiveness of cancer cells ( 14 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…be deemed a vital element in cervical cancer pathogenesis (23). Epithelial-mesenchymal transition was an important step in the process of cervical-epithelial carcinogenesis (24). The study of Xie et al also showed that the 2M checkpoint pathway was associated with CESC (25).…”
Section: Discussionmentioning
confidence: 99%
“…In the study of Xiong et al., the Rb-E2F pathway could be deemed a vital element in cervical cancer pathogenesis ( 23 ). Epithelial–mesenchymal transition was an important step in the process of cervical–epithelial carcinogenesis ( 24 ). The study of Xie et al.…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, the E6 protein binds p53, a major negative regulator of cell growth. The loss of p53 activity leads to uncontrolled cellular cycling, allowing chromosomal mutations to accumulate without DNA repair [ 31 ]. On the other, E7 protein targets p130, another negative cell-cycle regulator, thereby increasing cell growth and promoting uncontrolled proliferation [ 32 ].…”
Section: Natural History Of Hpv Infectionmentioning
confidence: 99%